ACCOUNTABILITY FOR HUMAN RIGHTS VIOLATIONS IN NIGERIA’S COUNTERINSURGENCY AGAINST BOKO HARAM: PROBLEMATISING THE OPTIONAL PROTOCOL TO THE INTERNATIONAL COVENANT ON CIVIL AND POLITICAL RIGHTS - Olusola Babatunde Adegbite (Padjadjaran Journal of International Law, 2021)
AbstractThe major objective of this Article is to examine the extent to which the accountability mechanism under international law is sensitive, and responsive to the challenges of accessing domestic remedies by victims of human rights violations in Nigeria’s counterinsurgency against Boko Haram. It explores the extent to which the current framework has enabled and facilitated efforts of victims in this wise especially those of poor, weak and defenceless victims. In this article, we make a case that the inability of international law under the auspices of the Optional Protocol to the International Covenant on Civil and Political Rights (ICCPR), to bring the perpetrators of heinous abuses in the counterinsurgency operations to book, is as a result of the deficiency in the complaint procedure, which is largely state-centred and a gap in the current framework. This article therefore proposes the view that remedies for victims in this conflict can be better realised, not just by viewing them as obligations that States are encouraged to fulfil within the confines of their sovereign status, but more importantly by crafting them within a framework of supranational legitimacy in which States can indeed be held accountable and compelled to meet their obligations. Keywords: Accountability, Human Rights, Boko Haram, Counterinsurgency, Optional Protocol. AbstrakTujuan utama dari artikel ini adalah untuk mengkaji sejauh mana mekanisme pertanggungjawaban dalam hukum pidana internasional dapat mengakomodasi tantangan dalam mengakses sistem kompensasi domestik bagi korban pelanggaran HAM dalam konflik pemberontakan Boko Haram di Nigeria. Tulisan ini menyelidiki bagaimana kerangka kerja yang ada saat ini memberikan ruang dan memfasilitasi korban dalam aspek tersebut, terutama mereka yang miskin dan rentan. Tulisan ini berargumen bahwa ketidakmampuan hukum internasional untuk membawa para pelaku kejahatan HAM berat dalam pemberontakan tersebut untuk bertanggung jawab atas kejahatan mereka terhadap korban adalah hasil dari kecacatan dalam prosedur pengaduan hukum pidana internasional, yang memang terfokus pada negara dan kurang mengakomodasi jenis-jenis konflik modern. Maka dari itu, tulisan ini mengusulkan perspektif dimana kompensasi kepada korban dari konflik pemberontakan ini dapat direalisasikan dengan lebih baik, dengan cara memasukkan pertanggungjawaban ini ke dalam legitimasi supranasional sehingga negara dapat dimintai pertanggungjawaban dan diwajibkan untuk memenuhi kewajiban mereka. Kata Kunci: Pertanggungjawaban, Hak Asasi Manusia, Boko Haram, Pemberontakan, Protokol Pilihan